The Pemanfaatan Pendapatan Non Halal Sebagai Sumber Pendanaan CSR Pada Perbankan Syariah Di Indonesia - Hanafil Haq Aninda (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
The background of this research is the emergence of a perception in our society that considers Islamic banking in its management to be the same as conventional banking. This is related to the existence of non-halal income in Islamic banking. Meanwhile, the control of sharia banking must follow the rules following sharia principles regulated in the DSN-MUI Fatwa and supervised by the Sharia Supervisory Board. Based on this reality, researchers are interested in studying the Utilization of Non-Halal Income as a Source of CSR Funding in Islamic Banking in Indonesia. This study uses descriptive qualitative research methods. The primary data source is the Statement of Financial Accounting Standards (PSAK 101) Presentation of Sharia Financial Statements and Fatwa DSN MUI NO: 123/DSN-MUI/XI/2018 Concerning Use of Funds That Should Not Be Recognized as Income for Sharia Financial Institutions, Sharia Business Institutions, and Islamic Economic Institutions. The results of the study indicate that the use of non-halal income as a source of CSR funding in Islamic banking is allowed because some are intended for the community's social needs.